WORKPLANS: Workshop on Planetary Nebula Observations - Isabel Aleman; Jeronimo Bernard-Salas; Joel H. Kastner; Toshiya Ueta; Eva Villaver (Galaxies, 2020)
This workshop is the second of the WORKPLANS series, which we started in 2016. The main goal of WORKPLANS is to build up a network of planetary nebulae (PNe) experts to address the main open questions in the field of PNe research. The specific aims of the WORKPLANS workshop series are (i) to discuss and prioritize the most important topics to be investigated by the PN community in the following years; (ii) to establish a network of excellent researchers with complementary expertise; (iii) to formulate ambitious observing proposals for the most advanced telescopes and instrumentation presently available (ALMA, SOFIA, VLT, GTC, HST, etc.), addressing those topics; and (iv) to develop strategies for major proposals to future observatories (JWST, ELT, SPICA, Athena, etc.). To achieve these goals, WORKPLANS II brought together experts in all key sub-areas of the PNe research field, namely: analysis and interpretation of PNe observational data; theoretical modeling of gas and dust emission; evolution from Asymptotic Giant Branch stars (PNe progenitors) to PNe; and the instrumentation and technical characteristics of the relevant observatories.